Pharmacokinetic aspects of Tert-Butylaminoethyl disulfide, an experimental drug against schistosomiasis in mice - Andrade,M. M. Guerra (1989)
A preliminary study of the pharmacokinetic parameters of t-Butylaminoethyl disulfide was performed after administration of two different single doses (35 and 300 mg/kg) of either the cold or labelled drug. Plasma or blood samples were treated with dithiothreitol, perchloric acid, and, after filtration, submitted to further purification with anionic resein. In the final step, the drug was retained on a cationic resin column, eluted with NaCl 1M and detected according to the method of Ellman (1958). Alternatively, radioactive drug was detected by liquid scintillation counting. The results corresponding to the smaller dose of total drug suggested a pharmacokinetic behavior related to a one open compartment model with the following parameters: area under the intravenous curve (AUC i.v.):671 ± 14; AUC oral: 150 ± 40 µg.min. ml [raised to the power of -1]; elimination rate constant: 0.071 min [raised to the power of -1]; biological half life: 9.8 min; distribution volume: 0.74 ml/g. For the higher dose, the results seemed to obey a more complex undertermined model. Combining the results, the occurence of a dose-dependent pharmacokinetic behavior is suggested, the drug being rapidly absorbed and rapidly eliminated; the elimination process being related mainly to metabolization. The drug seems to be more toxic when administered I.V. because by this route it escapes first pass metabolism, while being quickly distributed to tissues. The maximum tolerated blood level seems to be around 16 µg/ml.